Differential learning in sports games: a systematic review of a empirical research - Burkaitė, Greta; Paulauskas, Rūtenis (Pedagogika, 2025)
Differential learning (DL) is a motor learning method emphasizing practice variability and shows promising enhancement of performance in sports games. This systematic review analyzes research on DL interventions, suggesting that it accelerates skill acquisition compared to traditional methods. A systematic search of relevant databases identified peer-reviewed articles focusing on DL, non-linear pedagogy, and constraint-led approaches. Studies demonstrate DL’s positive impact on physical, technical, and cognitive skills across various game sports. By encouraging exploration of diverse movement solutions, DL fosters efficient skill acquisition, adapting techniques to individual athletes and game contexts. This adaptability contrasts with repetitive drills, promoting creativity and enhancing decision-making under various constraints. DL forces athletes to adapt, developing a flexible cognitive framework crucial for performance in dynamic game environments. This review concludes that DL is a promising training method, enhancing physical, technical, and cognitive skills. Further research should explore optimal DL implementation across different sports and athlete populations, investigating the balance between variability and specificity, and long-term effects on skill retention and transfer.